Description of Cadre Services for Elderly Participants in the Posyandu Lansia Nagari VII Koto Talago Kabupaten Lima Puluh Kota - Ikhsan Ikhsan; Irmawita Irmawita; Wirdatul Aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is background by good service towards cadre service toward the Posyandu elderly participant at Posyandu Nagari VII Koto Talago Guguak Sub-district of Lima Puluh Kota. The purpose of the study describes the benefits of services include: (1) information services, (2) facilities services, (3) health services. This type of research is descriptive quantitative. The population in the study amounted to 60 people. The sampling technique in this research is the cluster random sampling method, with 30 samples. The collection technique is a questionnaire, while the data collection tool uses a list of statements. The results showed that the benefits of cadre service according to members are very good: (1) excellent information service, (2) excellent facility service, (3) excellent health service. Suggestions for the delivery of services provided to the cadres to the participants are continuously improved so that participants feel happy in the service.Keywords: Cadre Service, Information, Facility, Health